GAGASAN GOLD DINAR PADA KEBIJAKAN EKONOMI MALAYSIA PASCA KRISIS EKONOMI ASIA 1997 ERA MAHATHIR - Enggar Prafitta Siwi (2013)
The Asian economic crisis, which occurred in 1997, hit the Malaysian and neighbouring countries ecomonic badly. The crisis in Malaysia was not merely due to the weakness in its economic fundamentals, but also due to the contagion and volatility effects particularly originated from Thailand. And Malaysia recover quickly from crisis. In the process of economic recovery, Malaysia is searching for an alternative solution to decrease the possibilities of being attacked by crisis. Mahathir Mohammad as